2001
DOI: 10.1093/jexbot/52.354.145
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock‐mediated APX gene expression and protection against chilling injury in rice seedlings

Abstract: Rice (Oryza sativa L.) seedlings, when kept at 42 degrees C for 24 h before being kept at 5 degrees C for 7 d, did not develop chilling injury. Chilling resistance was enhanced in parallel with the period of heat-treatment. The level of APX activity was higher in heated seedlings whereas CAT activity was decreased by heat stress. There was no significant difference in SOD activity between heated and unheated seedlings. The elevated activity of APX was sustained after 7 d of chilling. The cytosolic APX gene exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
105
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(116 citation statements)
references
References 34 publications
8
105
0
1
Order By: Relevance
“…Among the many processes that have been studied and published, the regulating role of kinases dependent on calcium and activated by cold temperature exposition (Saijo et al, 2000;Martín & Busconi, 2001); the involvement of abscisic acid as a signalling molecule (Lee et al, 1995); and the levels of activation of the enzymes associated to oxidative stress such as ascorbate peroxidase (Sato et al, 2001), catalase and glutathione reductase (Kang & Saltveit, 2002) may be cited. Despite the lack of knowledge regarding the germination period of rice, the existence of different physiological mechanisms involved with cold tolerance at the vegetative period is an indication that along the germination phases, different processes may also be affected, implying in different tolerance mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…Among the many processes that have been studied and published, the regulating role of kinases dependent on calcium and activated by cold temperature exposition (Saijo et al, 2000;Martín & Busconi, 2001); the involvement of abscisic acid as a signalling molecule (Lee et al, 1995); and the levels of activation of the enzymes associated to oxidative stress such as ascorbate peroxidase (Sato et al, 2001), catalase and glutathione reductase (Kang & Saltveit, 2002) may be cited. Despite the lack of knowledge regarding the germination period of rice, the existence of different physiological mechanisms involved with cold tolerance at the vegetative period is an indication that along the germination phases, different processes may also be affected, implying in different tolerance mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with our results, SOD also has been shown to be down-regulated at the protein and transcript levels by several oxidative stresses [48] or heat [56], respectively. In addition, Sato et al [57] reported that SOD activity was not altered in rice seedlings exposed to heat (427C). These results suggest that SOD responds to thermal stress in a complex manner or that isoforms could be differentially regulated.…”
Section: Redox Homeostasismentioning
confidence: 99%
“…This enzyme was induced by cold in fruitfly (Drosophila melanogaster; Duncker et al, 1995). Because chilling induces oxidative stress (Sato et al, 2001), it is possible that the sugarcane XDH is induced in response to oxidative stress generated by cold exposure. Another protein related to antioxidant metabolism is copper/zinc SOD (Cu/ZnSOD).…”
Section: Cold-responsive Genes In Sugarcanementioning
confidence: 99%